Hypertrophic mononeuropathy. Issue 1 (January 1974) - Hawkes, C. H.; Jefferson, J. M.; Jones, E. L.; Smith, W. Thomas
Abstract : A case of hypertrophic mononeuropathy is described in a 19-year-old female. The entity is very rare as only three previous cases have been reported. The light and electron-microscope appearances resemble those of progressive hypertrophic polyneuritis.